Advances and challenges in poliomyelitis vaccines: a comprehensive review of development, production, and global deployment - Liang, Jia; Zhang, Qi; Li, Yanan; Wang, Lili (Frontiers in Public Health, 2025)
Poliomyelitis has been a significant global health challenge for centuries. Since the launch of the Global Polio Eradication Initiative (GPEI) in 1988, remarkable progress has been achieved, with wild poliovirus (WPV) cases reduced by over 99%. However, challenges persist, including endemic transmission in conflict zones, the emergence of vaccine-derived polioviruses (VDPVs), and the complex logistics of vaccine production and distribution. This review synthesized the latest advancements in poliovirus vaccine development, production, and global deployment. Specific topics include the historical milestones of inactivated poliovirus vaccine (IPV) and oral poliovirus vaccine (OPV), innovations in next-generation vaccines such as novel OPV (nOPV2), intradermal IPV (IIPV), virus-like particle (VLP) vaccines, and mRNA vaccines, as well as critical considerations in manufacturing, quality control, and regulatory compliance. We also examined global strategies for vaccination campaigns, cold chain management, and eradication-endgame planning, alongside emerging challenges like VDPVs outbreaks, funding constraints, and geopolitical barriers. The significance of sustained global cooperation, equitable resource allocation, and technological advancement are essential to achieving a polio-free world, with the integration of scientific innovation with public health strategies. The lessons and insights presented herein inform polio eradication efforts, providing a blueprint for future disease eradication initiatives. The importance of resilience, adaptability, and community engagement was also emphasized for global health governance.